The Effect of Transformational Leadership Style on Organizational Civic Behavior Among Teachers - Syamsiyah, Munawaratus; Aisyah , Nur; Thelma, Chanda Chansa (Universitas Nurul Jadid, 2024)
This research focuses on understanding how transformational leadership affects teacher behavior, as well as its implications in the development of more effective leadership practices in the school environment. This research was conducted at MI Nurul Yaqin using a quantitative approach with a correlational method. Data was collected through questionnaires given to teachers at the school, which asked about their perceptions of transformational leadership and participation in Organizational Citizenship Behavior (OCB). In addition, in-depth interviews were also conducted to understand more deeply. The results showed a positive relationship between transformational leadership and OCB among teachers at MI Nurul Yaqin. The analysis confirmed that the stronger teachers' perceptions of transformational leadership, the higher their involvement in voluntary behavior in schools, including in MI Nurul Yaqin. In addition, specific aspects such as the development of an inspiring vision also have a significant effect on teacher participation in OCB in the school. However, it is also important to note that other factors such as organizational culture and other leadership support may also influence teachers' contribution in creating an inclusive and dynamic school environment in MI Nurul Yaqin. The implications of this study emphasize the importance of transformational leadership in encouraging teacher volunteering behavior (OCB) in schools, including in MI Nurul Yaqin, and highlight that the development of an inspiring leadership vision can stimulate teacher participation in OCB in the school environment. The implications of this study emphasize the importance of transformational leadership in encouraging teacher volunteer behavior (OCB) in schools.